A Systematic Literature Review On Safe Health Information Technology Use Behaviour - Lizawati, Salahuddin; Zuraini, Ismail; Wardah, Zainal Abidin (Penerbit UTM Press, 2016)
The implementation of health information technology (IT) is one of the strategy to improve patient safety due to medical errors. Nevertheless, inappropriate use of health IT may have serious consequences to the quality of care and patient safety. Most of the previous studies have been focused on the sociotechnical factors contributed to health IT related errors. Little focus has been given on the use behavior that influence the safety of health IT adoption. In order to address this gap, this study investigates the use behavior that influence the safety of health IT adoption. Systematic literature review was conducted to identify articles pertinent to safety of health IT. Science Direct, Medline, EMBASE, and CINAHL database were searched for reviews relevance articles. A total of 23 full articles were reviewed to extract use behavior that influence the safety of health IT adoption. Workarounds, adhere to procedure, vigilant action, and copy and paste behavior were discerned as the significance use behavior that influence health IT safety adoption. This study may be of significance in providing useful information on how to safely practice health IT adoption.